Thātuppathīpikā r̄ư photčhanānukrom Bālī-Thai : phan̄æk thāt, prak̨ōp dūai lak waiyāk̨ōn chan sūng - Thēpdarunānusit (Thawī), Lūang (Mahāmakutrātchawitthayālai, 1991)
Pali-Thai dictionary, including Pali morphology.